Mental Health Representation in Jennifer Niven’s "All the Bright Places" (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
This study analyzed the trauma of the main characters caused by traumatic experiences in the novel All The Bright Places By Jennifer Niven. It explained how the trauma portrayed in which it is explained as traumatized responses that the main character experienced. it used psychoanalytic perspectives of trauma from Cathy Caruth and qualitative approach to create the analysis. The theory was used to classify the responses of trauma are Anxiety, Avoidance, and Arousal. The study also aimed to find out how to the main character deal with the trauma that affects her daily life. The result has found out that the main character have shown the three responses of trauma in the novel, and it also has found out the connection of traumatized people in which it leads the main character to use the force on her grief to deal with the trauma.